Prevalence assessment of root dilaceration in permanent incisors - Beatriz Feitosa da Silva; Luciana Ellen Dantas Costa; Ricardo Villar Beltrão; Tânia Lemos Rodrigues; Ricardo Lombardi de Farias; Rejane Targino Soares Beltrão (Dental Press Editora, 2012)
INTRODUCTION: Root dilaceration is a dental anomaly characterized by an abnormal curvature of the dental root, which can cause problems during eruption and complications in the orthodontic and endodontic treatment or extraction. OBJECTIVE: The aim of this study was to determine the prevalence of root dilaceration in permanent incisors in an oral radiology clinic in the city of João Pessoa / PB, Brazil. METHODS: The sample consisted of 548 patients who allowed assessments of their dental radiographs, a total of 3,948 examined teeth. Each tooth was examined according to the occurrence of root dilaceration, regarding type (mild, moderate or severe), root third that it was in and direction of the root. The angle formed by the root deviation in relation to the long tooth axis was obtained by means of a diagram printed on transparent acetate, placed over the radiograph. RESULTS: The results were analyzed with SPSS software (Statistical Package for Social Sciences) version 13.0, performing an exploratory data analysis. The prevalence of root dilaceration in the studied sample was 1.03% (41 cases), with higher incidence in males (65.8%), being the superior lateral incisor the most affected teeth (78%). The most prevalent type of root dilaceration was the mild one (73.1%), occurring more in the apical third (90.2%) and with distal direction of the root (95.1%). CONCLUSION: Considering these results, it is emphasized the importance of performing a diagnostic radiographic examination prior to planning a treatment in permanent anterior teeth. INTRODUÇÃO: a dilaceração radicular é uma anomalia dentária caracterizada por uma curvatura anormal na raiz do dente que pode causar problemas na erupção e complicações durante movimentação ortodôntica, tratamento endodôntico ou exodontia. OBJETIVO: o objetivo do presente trabalho foi verificar a prevalência da dilaceração radicular em incisivos permanentes, em uma clínica de radiologia odontológica da cidade de João Pessoa/PB. MÉTODO: a amostra foi constituída de 548 pacientes que possibilitaram avaliações em suas radiografias dentárias, totalizando 3948 dentes examinados. Examinou-se cada dente segundo a ocorrência de dilaceração radicular, com relação ao tipo (discreta, moderada ou severa), o terço radicular em que se encontrava e a direção da raiz. A angulação formada pelo desvio da raiz em relação ao longo eixo do dente foi obtida por meio de um diagrama impresso em acetato transparente, colocado sobre a radiografia. RESULTADOS: os resultados foram analisados no programa SPSS, efetuando-se uma análise exploratória dos dados. A prevalência da dilaceração radicular na amostra estudada foi de 1,03% (41 casos), com maior incidência no sexo masculino (65,8%), sendo os incisivos laterais superiores os dentes mais acometidos (78%). O tipo de dilaceração radicular mais prevalente foi a discreta (73,1%), ocorrendo mais no terço apical (90,2%) e com direção distal da raiz (95,1%). CONCLUSÃO: diante desses resultados, ressaltam-se a importância da realização prévia de um exame radiográfico de diagnóstico ao planejar um tratamento em dentes permanentes anteriores.